EXAMINATION IN THEORY OF ACCOUNTS. - Zlatkovich, Charles T. (The Accounting Review, 1959)
The article reports that the examination in theory of accounts of the May 1959, Uniform Certified Public Accountants was given on May 15, 1959. There were two groups in the question. The estimated time allowances are approximately proportional to the point values of the questions, the total of which for this examination is 100. The examinee is required to answer all questions in the first group. In group one of the question paper, on a lined sheet of paper the examinee is required to number the first ten lines from 1 through 10. The examinee is to select the graph, which matches the numbered factory cost or expense data and write the letter identifying the graph on the appropriate numbered line. In the second question, in the preparation of the consolidated balance sheet of a hypothetical parent corporation and its subsidiaries a decision must be reached concerning the inclusion or exclusion of each of them as a member of the consolidated group. A common criterion is the percentage of voting stock owned by the parent company. Answers to every question are also given in the article.